Art Together, Prayer Together: Relational and Revelatory Practices of Joseph Beuys, Dietrich Bonhoeffer and Leslie Iwai - Burke, Meaghan (Religions, 2023)
This paper investigates a theology of prayer embedded within social and artistic practice. It considers how conceptual art broadened social possibilities for art, and how for Joseph Beuys and later Leslie Iwai, these possibilities probe spiritual realities. Beuys’ democratic methodologies, considering everyone as performing the world-shaping work of the artist, were central to his practice and described by Beuys as representations of Christ. In Life Together, the artist’s contemporary, Dietrich Bonhoeffer offers his own approach to Christ’s presence within sociality. The book reflects on his time directing a seminary where communal life was not only shaped by spiritual exercises like prayer, but also enriched by the arts. Consequently, one may read Life Together as grounding for socially and spiritually attuned artistic endeavours. This has been the case in Leslie Iwai’s conceptually and communally motivated artistic practice, which has developed alongside prayer practices and her own readings of Life Together. Social-spiritual features of Beuys’ conceptual art—seeing Christ and one another concurrently—are extended in Bonhoeffer’s articulation of prayer—not only revealing God and each other but also a means of presenting one another to God. Affinities between conceptual art and prayer emerge: both may be disclosive, holding together seen and unseen realities. Iwai can be seen to work from a conceptual mode of social-spiritual disclosure, and from consonant revelatory and intercessory practices of prayer echoing those of Bonhoeffer’s Life Together.